Concepts of Social Destruction Philosophical Analysis - G. Bekmurodova (International Journal on Integrated Education, 2022)
The article states that by the beginning of the new century, human society has entered a qualitatively new stage of its development. The social problems and negative processes that arise at this stage cause serious concern about their complexity and the scale of the consequences. In this regard, there is a need to generalize reflections on the essence and causes of destructive situations in order to determine the patterns of these processes. The article asserts that religious and philosophical views on the essence of destructive processes in the being of nature, society and man, the theoretical conclusions of G.V.F.Hegel, F.Nietzsche, Z.Freud, M. Horkheimer, T. Adorno, G. Marcuse and E. Fromm can serve as a reliable theoretical and methodological basis for a systematic analysis of today's regressive and crisis processes and factors, negative and destructive phenomena.